Exile and suffering : reading Psalm 77 in African context - Kamuwanga, Liswanisu (Old Testament Essays, 2007)
Reeling from the collapse of the kingdom and subsequent exile to Assyria and Babylon, the Israelites and people of Judah composed songs and prayers addressed to Yahweh. Disorientation arising from this tragic event gradually gave way to confidence and reorientation because the focus shifted from a situation of hurt to Yahweh's acts in Israel's history. In the Exodus, Yahweh had demonstrated his power by ending Israel's oppression in Egypt. This event is actualized during the exilic and post-exilic period to assure the disillusioned community of Yahweh's unchanging faithfulness. By bridging the historical gap between the biblical text and the contemporary African context, a comparative reading of Psalm 77 illuminates the darkness of colonialism and post-colonial failure and suffering. This reading yields hope to the despondent multitudes regarding Yahweh's concern for them not only in terms of future involvement but also in terms of his intervention and presence in contemporaryappalling contexts.
free